Leaching of Alumina From Aluminum Bearing Ores - John I. Choi; R. E. Johnson; Bruce E. Kurtz; Anatoli Omelian; B. R. Palmer; Y. Topkaya (Society for Mining, Metallurgy & Exploration, 1993)
This paper relates to hydrometallurgical studies on the recovery of soluble aluminum values from aluminum-bearing ores, i.e., Georgia clays. At least 50% of the soluble alumina values were recovered by leaching the calcined clays from aqueous solutions, comprising simultaneously contacting a stream containing an effective amount of a reducing agent such as sulfur dioxide and a stream containing an effective amount of an oxidizing agent such as chlorine gas for a time sufficient to dissolve alumina. The recovery of alumina from this aqueous slurry of the calcined clay by leaching with sulfur dioxide and chlorine gas showed much better results than that by leaching with concentrated sulfuric acid and/or concentrated hydrochloric acid at 100O C. The leaching reactions between the aqueous slurry of the calcined clay, chlorine gas, and sulfur dioxide were strong exothermic reactions for several hours, requiring no external heating.